Loud and Clear : Effective Language of Instruction Policies for Learning - World Bank (Washington, DC, 2022)
Part 1 addresses why we should care about LoI (Language of Instruction) issues and the major challenges involved. Its four sections are entitled: (i) why should we care (ii) how big is the problem (iii) the role of political economy; and (iv) diverse LoI contexts. Part 2 presents existing solutions (in section 5) and proposes a detailed way forward for the WB Education Global Practice (section 6). It should be noted that the paper does not claim to possess or propose a complete set of technical solutions for the myriad of difficult policy issues involved. By enhancing engagement and devoting adequate resources to the problem, existing solutions will be deployed, and new solutions devised. Increased partnership and knowledge sharing will be part of this, as will be the testing of innovative approaches. The new approach will involve learning at the individual and institutional level, with an intensity of engagement commensurate with the urgency of the issue.